Controle da saúde cardiovascular na estratégia de saúde da família - Tavares, Gilberto Andrade (2022)
INTRODUCTION In Brazil, the Unified Health System (SUS) guides public health care, and the Family Health Strategy (FHS) is its main access, with 60% of the population linked to it. The surveillance of risk factors for cardiovascular diseases (CVD) is the responsibility of the ESF. In 2010, the American Heart Association (AHA) proposed seven Cardiovascular Health (CVH) metrics, which were divided into "ideal", "intermediate" and "poor" levels. Since then, several studies around the world have shown that five or more metrics at the "optimal" level of CVH reduced CVD mortality. As a means of diagnosing and monitoring these metrics, mobile health tools can support shared decision-making, with return by telemonitoring, implying the reduction of cardiovascular risk. OBJECTIVES To measure the seven cardiovascular health metrics recommended by the AHA, verify the associated factors and create an application for use in the FHS. METHOD Cross-sectional study among FHS users, through a questionnaire applied by the interviewer, divided into blocks. In the multivariate statistical analysis, the main dependent variable "CVH control" was categorized as "controlled" (>5 optimal level metrics in CVH) and "uncontrolled" (< 5 optimal level CVH metrics). For the development of the "Cardiovascular Health" application, we chose the User- Centered Design method, Dart programming language, Flutter framework and Firebase database. RESULTS Among the 400 patients evaluated, only 32.5% had "controlled" CVS. Overall, 92% did not smoke, 79.3% had controlled blood glucose, 70.8% were physically active and 66.5% had controlled cholesterol. Only 35% had controlled blood pressure, similar to BMI (30.8%), and 10.8% maintained a diet at the "ideal" level. The adjusted multivariate analysis identified that being female (RCa: 2.07; 95% CI: 1.20 - 3.60), under 45 years (RCa: 1.61; CI 95%: 1.15 - 2.28), ) and receive guidance on care from family members/friends about their health (RR: 1.28; 95% CI: 1.15 - 2.28) were positively associated with the "control" of CVH, while having a higher number of children (RR: 0.91; 95% CI: 0.84 - 0.95) reduced this "control". After downloading the app, the user agreed to its usage rules. Then, each metric was indicated at the "good", "can improve" and "need to improve" levels. Next, a PDF document was generated for each level in corresponding SCV, being shared via e-mail. CONCLUSION In the population analyzed, there is a low overall prevalence of ideal CVH metrics, with the majority at the "ideal" level for smoking, glycemia, physical activity and cholesterol. Blood pressure and diet were at the "intermediate" level and BMI at the "bad" level. Being a woman, young and sharing with neighbors and family decisions about their health positively influenced the control of CVH. Having more children reduced control of these metrics. We can indicate that greater attention from health authorities should contribute to the reduction of cardiovascular events. Our application will provide physicians and other health caregivers from the FHS with the best decisions for monitoring and health interventions of the assisted population.